Studi Teologis Doktrin Tritunggal dalam Perspektif Teologi Baptis dan Implikasinya bagi Iman Umat Baptis - ; Bobby Hartono (Syntax Idea)
The Doctrine of the Trinity, or the Triune God, is one of the most essential and fundamental teachings in Christianity, including for Baptists. However, it should be acknowledged that this doctrine is not explicitly written in the Bible but is rather implied through various events. The Doctrine of the Trinity in Christian theology often becomes a point of contention both within and outside the Christian community because it is frequently perceived as complex and difficult to comprehend. As a result, many Christians, including clergy, attempt to avoid discussing this core doctrine and consider it a difficult subject best left to academics. Consequently, some Christians may affirm the formulation of this doctrine without a proper understanding because they do not grasp the practical aspects of this teaching. Therefore, with the help of this article, the author aims to investigate and ensure a proper and comprehensive understanding of the Doctrine of the Trinity from the perspective of Baptist theology. This way, we, as Christians, especially Baptists, can apply the Doctrine of the Trinity in our daily lives with a clear understanding. In this research, a qualitative descriptive method is used, along with a literature review. For Baptists, the God revealed in the Bible is the Triune God, and this is the truth that must be understood by Baptists specifically and Christians in general.